Análisis de daño del gusano cesto (Oiketicus kirbyi Lands) en el cultivo de banano (MUSA AAA) en el Ecuador - León Escobar, Moisés Saul (2024)
The research details the analysis of damage from the basket worm (Oiketicus kirbyi Lands) in the banana crop (MUSA AAA) in Ecuador. The objectives were to identify the symptoms and damage caused by the basket worm in banana crops and describe the control methods of the basket worm in banana crops. The conclusions determine that the basket worm is a polyphagous insect that feeds on various crops and wild plants, including musaceae (Musa spp.). The larva has the ability to feed on a wide range of plant species, including crops and weeds. When the larva descends to the foliage of the plant, it immediately begins its feeding process. The larvae are often transported long distances by air currents, animals or vehicles. Larvae in early stages exhibit limited autonomous mobility. The basket worm can pose a significant problem, as it is an extremely polyphagous insect and several of its hosts are plants of agricultural, forestry and ornamental importance. During its larval stage, the insect shows a high level of voracity, consuming around 304.5 square centimeters of foliage. To improve monitoring, it is suggested to remove plant baskets during the winter season to eradicate eggs. During the spring season, in the presence of caterpillars, it is recommended to apply a biological insecticide to the plant. Bacillus thuringiensis is the most effective and most used biological control method for lepidopteran pests.